The duality of service: between honour and humiliation, between primary and secondary functions - Sternberg, G (Oxford University Press, 2014)
This chapter revisits a celebrated act of court ritual: the gesture of handing the king his chemise as he rose each morning. Re-contextualizing this gesture thematically, socially, chronologically, and functionally, I underscore the duality of such ‘honourable service’ and the degree to which it was shaped by extra-royal agendas even in the heyday of the Sun King. In place well before Louis XIV, these acts occurred in sub-royal as well as in royal settings; in the former, a more complicated perception of service emerges, of a humiliating task as well as a ‘prestige fetish’. Givers, moreover, were also receivers: each time an aristocrat was to hand the king the chemise, he would receive it from others; often, this was the more important interaction. The final section uncovers the macro-political stakes of these acts in the struggle of the Legitimated Princes to equate themselves with the legitimate princes of royal blood.